Pro Google Kubernetes Engine : network, security, monitoring, and automation configuration - Sabharwal, Navin; Pandey, Piyush (Apress L.P., 2020)
Discover methodologies and best practices for getting started with Google Kubernetes Engine (GKE). This book helps you understand how GKE provides a fully managed environment to deploy and operate containerized applications on Google Cloud infrastructure. You will see how Kubernetes makes it easier for users to manage clusters and the container ecosystem. And you will get detailed guidance on deploying and managing applications, handling administration of container clusters, managing policies, and monitoring cluster resources. You will learn how to operate the GKE environment through the GUI-based Google Cloud console and the "gcloud" command line interface. The book starts with an introduction to GKE and associated services. The authors provide hands-on examples to set up Container Registry and GKE Cluster, and you will follow through an application deployment on GKE. Later chapters focus on securing your GCP GKE environment, GKE monitoring and dashboarding, and CI/CD automation. All of the code presented in the book is provided in the form of scripts, which allow you to try out the examples and extend them in interesting ways. What You Will Learn Understand the main container services in GCP (Google Container Registry, Google Kubernetes Engine, Kubernetes Engine, Management Services) Perform hands-on steps to deploy, secure, scale, monitor, and automate your containerized environment Deploy a sample microservices application on GKE Deploy monitoring for your GKE environment Use DevOps automation in the CI/CD pipeline and integrate it with GKE Who This Book Is For Architects, developers, and DevOps engineers who want to learn Google Kubernetes Engine